Prospects of performing multiple-country comparison of dairy sires for countries not participating in Interbull international genetic evaluations - Torsell, Anne (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2007)
With the international trade of genetic material of dairy bulls there is a need for genetic evaluations performed internationally. For this reason Interbull and the Interbull centre was established, today 42 countries are members of the organization and 26 countries participating in one or several genetic evaluations.